Ectopic Expression of OsSta2 Enhances Salt Stress Tolerance in Rice - Kumar, Manu; Choi, Juyoung; An, Gynheung; Kim, Seong-Ryong (Frontiers in Plant Science, 2017)
Salt stress can severely reduce crop yields. To understand how rice (Oryza sativa) plants respond to this environmental challenge, we investigated the genes involved in conferring salt tolerance by screening T-DNA tagging lines and identified OsSta2-D (Oryza sativa Salt tolerance activation 2-Dominant). In that line, expression of OsSta2 was enhanced by approximately eight-fold when compared with the non-transformed wild type (WT). This gene was highly expressed in the callus, roots, and panicles. To confirm its role in stress tolerance, we generated transgenic rice that over-expresses OsSta2 under a maize ubiquitin promoter. The OsSta2-Ox plants were salt-tolerant at the vegetative stage, based on our calculations of chlorophyll fluorescence (Fv/Fm), fresh and dry weights, chlorophyll concentrations, and survival rates. Under normal paddy field conditions, the Ox plants were somewhat shorter than the WT control but had improved agronomic traits such as higher total grain yield. They were also more tolerant to osmotic stress and hypersensitive to abscisic acid. Based on all of these results, we suggest that OsSta2 has important roles in determining yields as well as in conferring tolerance to salt stresses.